Dysfunction of Resting-State Functional Connectivity of Amygdala Subregions in Drug-Naïve Patients With Generalized Anxiety Disorder - Wang, Mei; Cao, Lingxiao; Li, Hailong; Xiao, Hongqi; Ma, Yao; Liu, Shiyu; Zhu, Hongru; Yuan, Minlan; Qiu, Changjian; Huang, Xiaoqi (Frontiers in Psychiatry, 2021)
Objective: Although previous studies have reported disrupted amygdala sub-regional functional connectivity in generalized anxiety disorder (GAD), most of these studies were conducted in GAD patients with comorbidities or with drug treatment. Besides, whether/how the amygdala sub-regional functional networks were associated with state and trait anxiety is still largely unknown. Methods: Resting-state functional connectivity of amygdala sub-regions, including basolateral amygdala (BLA) and centromedial amygdala (CMA) as seed, were mapped and compared between 37 drug-naïve, non-comorbidity GAD patients and 31 age- and sex-matched healthy controls (HCs). Relationships between amygdala sub-regional network dysfunctions and state/trait anxiety were examined using partial correlation analyses. Results: Relative to HCs, GAD patients showed weaker functional connectivity of the left BLA with anterior cingulate/medial prefrontal cortices. Significantly increased functional connectivity of right BLA and CMA with superior temporal gyrus and insula were also identified in GAD patients. Furthermore, these functional connectivities showed correlations with state and trait anxiety scores. Conclusions: These findings revealed abnormal functional coupling of amygdala sub-regions in GAD patients with regions involved in fear processing and emotion regulation ,including anterior cingulate/medial prefrontal cortex and superior temporal gyrus, which provide the unique biological markers for GAD and facilitating the future accurate clinical diagnosis and target treatment.